First decentralize after regionalize - Vegas Pozo, José (2013)
In this essay I analyze problems of our society that are initiated from the Republic and their roots in colonialism. The centralism of Lima is the classic expression to the extent that high percentage concentrated in the centers of finance and marketing, health, education and hinders the development of the country. This generates the migration to Lima and then to mid-sized cities. Hence the urgent need to transverse regionalization.